On Lê’s formula in arbitrary characteristic - Garc´ıa Barroso, Evelia Rosa; Płoski, Arkadiusz (Analitic and Algebraic Geometry 4, 2022)
In this note we extend, to arbitrary characteristic, Lê’s formula (Calculation of Milnor number of isolated singularity of complete intersection. Funct. Anal. Appl. 8 (1974), 127–131).